A resilience safety climate model predicting construction safety performance. (November 2018) - Chen, Yuting; McCabe, Brenda; Hyatt, Douglas
Highlights: A construction safety climate model with resilience elements was developed. The model is named SCR in this paper. The interactions of the SCR factors on construction sites were demonstrated. The pivotal role of management commitment in safety performance was validated. The direct impact of safety awareness on safety performance was validated. Abstract: Safety climate has the potential to affect construction safety performance. The current focus of construction safety climate research has been on management commitment, safety rules and procedures, housekeeping and safety equipment, supervisor and coworker safety perception. However, other aspects, such as reporting and preparedness, that are also critical to safety performance, are rarely measured. In the meantime, safety plateau in the construction industry has been observed in many countries; and there are less and less injury data, which has made safety performance prediction more and more difficult. All of this has necessitated us looking for a new approach. Resilience, that is a concept under development, has shown its ability to continuously improve safety performance. Thus, to enhance the existing safety climate model, this paper developed a concept called Safety ClimateResilience (SCR ) by introducing resilience to safety climate. SCR is measured by seven dimensions including management commitment, supervisor safety perception, coworker safety perception, learning, reporting, anticipation, and awareness. Based on 431 self-administered surveys from 68 construction sites in Ontario, Canada, SCR measure model was validated and the interactions of the seven factors of SCR model were also investigated. This paper leads to several conclusions. First, a resilience safety climate model was built and firstly applied to the construction industry. Second, commitment from all organizational levels, from top management, to site level, and to individual level, is the key to promoting a better safety performance. Third, safety awareness is the most important individual factor affecting the safety performance of construction workers.